Shrines in a Fluid Space: The Shaping of New Holy Sites in the Ionian Islands, the Peloponnese and Crete under Venetian Rule (14th-16th Centuries) - Dermitzaki, Argyri (Mediterranean Art Histories, 2022)
In Shrines in a Fluid Space, Argyri Dermitzaki offers a study of the cultic phenomena and sites visited by late medieval pilgrims in the Ionian Sea, the Peloponnese and Crete.; Readership: All interested in the cultic phenomena in Corfu, Strophades, the Peloponnese and Crete, in cultural exchanges in the Mediterranean and in late medieval Holy Land pilgrimage.